2003
DOI: 10.1063/1.1577112
|View full text |Cite
|
Sign up to set email alerts
|

Spectrum and vibrational predissociation of the HF dimer. II. Photodissociation cross sections and product state distributions

Abstract: We study vibrational predissociation of the HF dimer both by a full coupled channels treatment as well as in the Fermi golden rule approximation. Photodissociation cross sections, linewidths, and rotational state distributions are computed for excitations from the ground state with rotational quantum numbers Jϭ1, Kϭ0 to monomer stretch excited states with JϭKϭ0, both for even and odd permutation symmetry. The resonances investigated include excitation of the hydrogen bond donor and acceptor stretches, as well … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
13
0

Year Published

2004
2004
2011
2011

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 28 publications
0
13
0
Order By: Relevance
“…In a previous study on the vibrational predissociation of HF dimer it was shown that the Fermi golden rule approximation gives linewidths and product-state distributions that are in good agreement with full coupled channels calculations. 42 The same study also showed that the use of quasibound states to compute line strengths for the transitions to the vibrationally predissociating states is justified. We therefore applied the same approximations to the HCl dimer.…”
mentioning
confidence: 89%
See 4 more Smart Citations
“…In a previous study on the vibrational predissociation of HF dimer it was shown that the Fermi golden rule approximation gives linewidths and product-state distributions that are in good agreement with full coupled channels calculations. 42 The same study also showed that the use of quasibound states to compute line strengths for the transitions to the vibrationally predissociating states is justified. We therefore applied the same approximations to the HCl dimer.…”
mentioning
confidence: 89%
“…As in our work on the photodissociation of the HF dimer, 42 the scattering wave function JM (Ϫ) j A j B j AB l is expanded in a space-fixed basis ͉( j A j B ) j AB l;JM ͘ SF , which is related to the body-fixed basis via a unitary transformation:…”
Section: ͑5͒mentioning
confidence: 99%
See 3 more Smart Citations